Predictive Model of Energy Consumption of a Home - Mrázek, Michal; Honc, Daniel; Sanseverino, Eleonora Riva; Zizzo, Gaetano (Springer Nature Switzerland AG, 2020)
The usage of the renewable energy sources and electric vehicles is rising which might result in a problem with the energy grid stabilization. Some works state that buildings contribute to the overall energy consumption by 20 – 40 % which makes them a great subject to study. Finding solutions for better energy manage-ment can have a significant impact on the energy sector. This work focuses on proposing a simplified model of a home considering main appliances, heating and cooling, a photovoltaic system, an electric vehicle and weather and solar irradi-ance forecasts. The model is created in MATLAB as a simulation script with de-fined parameters. It uses a 5 day weather forecast to predict energy demands of a home as well as expected energy generation by the photovoltaic panels. This model can be used to better understanding the energy demand of either a single building or a community of buildings put together based on the information about the outside environment. Another possibility is to use the model for predictive optimization in order to find better ways of energy usage in a building.
Prediktivní model energetické spotřeby domu
Keywords: home simulation; energy demand; weather forecast; simulace domu; energetická náročnost; předpověď počasí